2022
DOI: 10.3389/fphar.2022.932154
|View full text |Cite
|
Sign up to set email alerts
|

Recent findings in the regulation of G6PD and its role in diseases

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) is the only rate-limiting enzyme in the pentose phosphate pathway (PPP). Rapidly proliferating cells require metabolites from PPP to synthesize ribonucleotides and maintain intracellular redox homeostasis. G6PD expression can be abnormally elevated in a variety of cancers. In addition, G6PD may act as a regulator of viral replication and vascular smooth muscle function. Therefore, G6PD-mediated activation of PPP may promote tumor and non-neoplastic disease progression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…Moreover, SIRT5 regulates isocitrate to α-ketoglutarate (α-KG) by desuccinylating isocitrate dehydrogenase 2 (IDH2), thus supporting ROS scavenging activities. In addition, SIRT5, through deglutarylation, increases the activity of glucose 6-phosphate dehydrogenase (G6PD) via the pentose phosphate pathway (PPP) and promotes NADPH production [ 84 , 87 ]. Rapidly proliferating cells require metabolites from PPP to synthesize ribonucleotides and regulate gene expression.…”
Section: Sirt Proteins: An Overview Of Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SIRT5 regulates isocitrate to α-ketoglutarate (α-KG) by desuccinylating isocitrate dehydrogenase 2 (IDH2), thus supporting ROS scavenging activities. In addition, SIRT5, through deglutarylation, increases the activity of glucose 6-phosphate dehydrogenase (G6PD) via the pentose phosphate pathway (PPP) and promotes NADPH production [ 84 , 87 ]. Rapidly proliferating cells require metabolites from PPP to synthesize ribonucleotides and regulate gene expression.…”
Section: Sirt Proteins: An Overview Of Structure and Functionmentioning
confidence: 99%
“…Rapidly proliferating cells require metabolites from PPP to synthesize ribonucleotides and regulate gene expression. G6PD expression can be deregulated in a variety of cancers and act as a regulator of viral replication [ 87 ]. Recent studies have suggested that SIRT5 plays an important role as a proviral factor necessary for the efficient replication of acute respiratory syndrome coronavirus 2 (SARS-CoV-2) through its direct interaction with the viral Nsp14 protein [ 88 ].…”
Section: Sirt Proteins: An Overview Of Structure and Functionmentioning
confidence: 99%
“…Glucose-6-phosphate dehydrogenase (G6PD, glucose 6-phosphate: NADP (+) oxidoreductase, EC1.1.1.1.49) enzyme is the first and rate-limiting step in the pentose phosphate pathway (PPP). G6PD is an allosteric enzyme found in monomer, homodimer, and homotetramer forms and catalyzes the production of 6-phosphogluconolactone from glucose-6-phosphate (G6P) ( Meng et al, 2022 ). G6PD maintains the reduction of NADP + into coenzyme NADPH which is vital for various reductive biosynthetic reactions such as maintaining reduced glutathione (GSH), protection against reactive oxygen species (ROS), and detoxification of xenobiotics ( B Tandogan, 2011 ; Gao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 NADPH provides materials for tumor biosynthesis while reducing oxidative stress within tumor cells. [23][24][25] In some tumor cells, over 85% of the ribose produced in the PPP pathway for nucleotide synthesis is generated directly or indirectly by the nonoxidative PPP. 26 Thus, TKT, a key enzyme in the nonoxidative PPP, is essential for cancer cell survival and growth.…”
Section: Introductionmentioning
confidence: 99%
“…R5P serves as a precursor for the nucleic‐ and amino‐acid synthesis, influencing cancer cell metabolism and proliferation, and DNA damage response 21,22 . NADPH provides materials for tumor biosynthesis while reducing oxidative stress within tumor cells 23–25 . In some tumor cells, over 85% of the ribose produced in the PPP pathway for nucleotide synthesis is generated directly or indirectly by the nonoxidative PPP 26 .…”
Section: Introductionmentioning
confidence: 99%